Religious Families as Sources of Islamic Cultural Capital: Social Analysis in Islamic Religious Education, Analysis of Bourdieu's Social Theory - Ma`arif, Muhammad Anas; Sebgag, Saliha; Syamsi, Moh.; Alai, Ashimatul (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
This study examines the role of religious families as a source of Islamic cultural capital in shaping students’ religious identity and learning dispositions in Islamic Religious Education (PAI). Using the social theory framework of Pierre Bourdieu, particularly the concepts of social capital, cultural capital, and habitus, this study analyzes how religious values, knowledge, and practices are transmitted within families and influence students’ learning experiences. The study adopts a qualitative literature-based analytical approach to explore forms of religious practices within Muslim families, such as daily worship routines, parental role modeling, moral discussions, and participation in religious activities. The findings indicate that religious families function not only as normative institutions of religious teaching but also as strategic arenas for the formation and reproduction of Islamic cultural capital. These practices contribute to the development of religious habitus, Qur’anic literacy, moral discipline, and positive learning dispositions toward PAI. Furthermore, the accumulation of Islamic cultural capital within families strengthens students’ motivation, academic performance, and religious behavior in educational settings. In Bourdieu’s perspective, the transmission of religious values and knowledge within the family represents a mechanism of cultural reproduction that shapes students’ dispositions and positions within the educational field. Therefore, the success of Islamic Religious Education is not solely determined by school factors but is also strongly influenced by the strength of religious habitus and Islamic cultural capital formed within the family environment.